Comparison of Mangrove Biomass in Three Different Mangrove Ecosystem Locations in Maros Regency - Muhammad Yusran; Nita Rukminasari; Joeharnani Tresnati; Wilma Joana Carolina Moka (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
This study aims to analyze the variation in mangrove biomass across three locations in Maros Regency, South Sulawesi, namely Borongkalukua, Bonto Bahari, and Ampekale. Data collection was conducted using purposive sampling design, 27 observation plots (10×10 m; n=9 per location) were established to estimate biomass through Diameter at Breast Height (DBH) and species-specific allometric equations. Five mangrove species were identified, namely Rhizophora mucronata, Rhizophora apiculata, Avicennia alba, Avicennia marina, and Sonneratia alba. The two-way ANOVA results showed that species (p = 0.0003), location (p = 0.0266), and their interaction (p = 0.0065) had significant effects on biomass. The Kruskal–Wallis test also confirmed differences in median biomass among locations (p = 0.0104). Borongkalukua exhibited the highest biomass (302.57 Mg/ha) dominated by R. mucronata and R. apiculata, followed by Ampekale (223.20 Mg/ha) dominated by R. apiculata and S. alba, while the lowest biomass was recorded in Bonto Bahari (129.44 Mg/ha), dominated by A. marina. These variations in biomass reflect differences in species’ adaptive capacity to local environmental conditions. Overall, the findings emphasize that the interaction between species and location is a key determinant of mangrove biomass productivity.